DIMENSIONAMENTO DE RESERVATÓRIOS PARA SISTEMAS DE ABASTECIMENTO DE ÁGUA DA CHUVA PARA A REGIÃO DOS CAMPOS GERAIS TENDO EM VISTA CENÁRIOS DE MUDANÇAS CLIMÁTICAS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
The objective of this study was to size the reservoir for rainwater harvesting system in the Campos Gerais of Paraná according to the methodologies proposed by the ABNT (2007), considering the impacts of climate change projected until the end of the 21st century on the fifth report of the IPCC. On this paper, the methodologies for calculation of final volume of rainwater reservoir proposed by ABNT (2007) were used, as well the historical series of rainfall data and those projected for two possible climatic scenarios were used. Through the PGECLIMA_R tool, it was possible to project the precipitation levels predicted in the best and the worst climatic scenario by the end of the century, in order to size the reservoir and analyze the impacts caused by climate change under the final volume of the rainwater reservoir. It was concluded that the designer should take into account the expected climate changes for the design of storage reservoirs and the use of rainwater, since these presented large volume variations according to each applied methodology and for each simulated scenario. When designing future precipitation data, the PGECLIMA_R software presented itself as an important tool to be used in the area of civil construction, urban and development planning.
Keywords: captação de águas pluviais; NBR15527:2007; Alterações climáticas; reservatório de água da chuva; rainwater harvesting system; NBR15527:2007; climate change; rainwater reservoir; CNPQ::ENGENHARIAS::ENGENHARIA SANITARIA